Preferences regarding road transports of hazardous materials using choice experiments - any sign of biases? - Lena Winslott Hiselius (Lund University, School of Economics and Management, Department of Economics, 2005)
This paper uses the choice experiment approach to assess people's preferences regarding road transports of hazardous materials. In a mail survey, carried out in Stockholm, the capital of Sweden, changes in exposure to hazardous materials are used as a proxy for changes in accident risk. The results are analysed in the light of an earlier study on transports of hazardous materials by rail. Special attention is given to biases associated with the choice experiment method. The presence of hypothetical bias is studied by the use of self-reported degree of confidence that the respondent would vote the same way in a real referendum. The presence of a focusing effect is studied by an inclusion of information on other fatal risks. The indication is that there are no major differences in individual preferences for hazmat transported by rail or road. The estimates are also dependent on the confidence of stated choices and interpreting this dependence as a hypothetical bias, suggest that this type of bias tends to push estimated values downwards. The findings show that individual background data regarding transports of hazardous materials affect individuals in expected ways and there is no focusing effect.
Keywords: C25; D61; D81; R41; 330; Biases; Hazardous materials; Risk; Choice experiments